Inhalation risk of teachers to airborne microplastics exposure in indoor daycare centre - Muhammad Amiruddin, Shuhairi (2025)
The study addressed the problem of exposure to airborne microplastics (AMPs) in daycare centers, highlighting the potential health risks for teachers due to insufficient data on their presence. The research aimed to determine the concentration of MPs in indoor air, identify their I/O ratios, and explore the correlation between various factors influencing MP concentrations. Nine samples were collected from three daycare centres which located in Kuantan District, Pahang, the concentration of indoor AMP is markedly higher than the outdoor AMP where Daycare Centre B accounted for 89.79 MP/m3 (74.69- 109.17) MP/m3 indoor and 86.88 MP/m3 (69.38-90.10) MP/m3 outdoor and Daycare Centre C with median (IQR) indoor and outdoor AMP concentration was 161.88 (123.44-170.63) MP/m3 and 112.71 (81.56-121.25) MP/m3. The analysis revealed an average indoor-to-outdoor ratio of 1, indicating higher levels of MPs indoors than outdoor environments. Additionally, no significant correlations (p > 0.05) were found between indoor MP concentrations and driving factors (indoor air velocity, indoor temperature, indoor relative humidity, number of occupants, type of building, type of ventilation EDI ranges from 136.54 to 278.69 MP/kg-day. There is an inverse relationship between teacher bodyweight and EDI. The study concluded that daycare centers are critical environments for monitoring AMP exposure, emphasizing the need for improved air quality standards to protect teachers from developing chronic respiratory problems from prolonged exposure.